Diversity of Scleria (Cyperaceae) in Amazonian restinga in Pará state, Brazil - Schneider,Layla Jamylle Costa (2020)
Abstract This study aims to contribute to the knowledge on the taxonomy of Scleria in sandy coastal plains (restinga) in Pará state, Brazil. Material deposited in the herbaria of Museu Paraense Emílio Goeldi (MG), Embrapa Amazônia Oriental (IAN), and Instituto de Estudos Costeiros da Universidade Federal do Pará (HBRA) were analyzed and species were identified using relevant literature, protologues, and types available online. We recorded nine species of Scleria for restinga in the state: Scleria bracteata, S. gaertneri, S. hirtella, S. interrupta, S. macrophylla, S. microcarpa, S. reticularis, S. secans, and S. violacea. An identification key, descriptions, illustrations, and comments about diagnostic characters and geographic distribution are provided for these species.